Perivascular spaces around arteries exceed perivenous spaces in the mouse brain - Nina G. Smets; Shakira A. van der Panne; Gustav J. Strijkers; Erik N. T. P. Bakker (Scientific Reports, 2024)
Abstract The perivascular space (PVS) surrounds cerebral blood vessels and plays an important role in clearing waste products from the brain. Their anatomy and function have been described for arteries, but PVS around veins remain poorly characterized. Using in vivo 2-photon imaging in mice, we determined the size of the PVS around arteries and veins, and their connection with the subarachnoid space. After infusion of 70 kD FITC-dextran into the cerebrospinal fluid via the cisterna magna, labeled PVS were evident around arteries, but veins showed less frequent labeling of the PVS. The size of the PVS correlated with blood vessel size for both pial arteries and veins, but not for penetrating vessels. The PVS around pial arteries and veins was separated from the subarachnoid space by a thin meningeal layer, which did not form a barrier for the tracer. In vivo, FITC-dextran signal was observed adjacent to the vessel wall, but minimally within the wall itself. Post-mortem, there was a significant shift in the tracer's location within the arterial wall, extending into the smooth muscle layer. Taken together, these findings suggest that the PVS around veins has a limited role in the exchange of solutes between CSF and brain parenchyma.